Pemberdayaan Masyarakat melalui Teknik Konservasi Tanah dan Air dalam Upaya Mitigasi Dampak Perubahan Iklim - Naharuddin; Rahmawati Rahmawati; Ariyanti Ariyanti; Erniwati Erniwati; Muthmainnah Muthmainnah (Institut Pertanian Bogor, 2023)
Land use regulation and soil and water conservation techniques need to be intensified to minimize the impact of climate change, especially in controlling floods, erosion and landslides. The purpose of this service is to provide education to the public in efforts to mitigate the impact of climate change through environmentally friendly soil and water conservation technology. The method used in this service is a participatory educational and training method or educational and participatory approach with extension activities, training and technical guidance. The results of the service implementation have been carried out, namely: preparation, introduction of activities, implementation of counseling/training on the material: a) The benefits of increasing land productivity through soil and water conservation techniques and b) Introduction and several soil and water conservation techniques, namely vegetative techniques and terrace construction. the contours of the A frame model, in addition, an evaluation is carried out. Service activities provide benefits in increasing land productivity and assisting in planting arrangements according to contour lines and as a basis for making terraces.